Implantação de projeto de energia solar fotovoltaica em edifício federal em São Paulo - Kroetz, Adriana Santiago Souza (2023)
The right to electricity is a global issue of paramount importance, including the United Nations (UN) highlights the issue as an objective with SDG 07, which aims to ensure universal, reliable access, at tangible prices, to all referring to electricity services by 2030. To meet this goal, continuous efforts are required from the scientific community in the search for renewable, efficient, and economical alternatives. As for the theme, the Brazilian electrical matrix is sustainable, with 82.9% of the generation of electricity coming from renewable sources, however, this advance is extremely dependent on the hydroelectric source, which participates in the supply with 56.8% of the total produced in Brazil in 2021. Based on this scenario, it is necessary to analyze the diversification of the matrix, migrating higher percentages of meeting demand through other sources, to meet the demand for electricity. Therefore, in Brazil, the increased use of energy solutions from a renewable source other than hydroelectric power is made possible, among others, using solar energy, a source with the greatest growth prospects considering the country's solar potential. However, it is known that solar energy is known by the Brazilian population, but there is still no significant use of this energy, which represents only 2.5% of the total energy offered in Brazil in 2021. Among the reasons for the underutilization of photovoltaic solar energy in Brazil is the initial installation cost, and among the benefits for the user are the reduction in energy costs, property valuation, and the fact that the system is durable and requires low maintenance. It emphasizes the importance of public policies for the diversification of the matrix and the implementation of projects in its buildings, serving as an example for society. The public power sector in Brazil was responsible for 3.4% of the electricity consumed in 2021, a percentage that increased by 7.4%. Therefore, in view of the diversification of the Brazilian electrical matrix and the public sector's contribution to the subject, this study sought to analyze the photovoltaic solar energy project developed for a federal building. For the study, theoretical research was carried out based on a literature review on photovoltaic solar energy, later focusing on a case study of the construction work of the Military College of São Paulo (CMSP). To build and develop this study, data collection was done through documentary research and interviews, following a semi-structured script. The results showed that the development of buildings that incorporate the implementation of the solar PV system in their project contributes to the economy of public coffers, minimizing the use of electricity from consumption. The project was developed in 02 years, and the construction will be carried out in the period from 2020 to 2024, and the implementation of the solar PV system will initially supply the gym. Therefore, through the study of the CMSP project, it was verified that there are possibilities for expanding the use of photovoltaic energy from public policies, which can contribute as an example of promoting the distributed generation of photovoltaic energy, so that the solar energy scenario in Brazil is attractive to new investors.